Biology and Morphometrics of Tessaratoma javanica Reared on a Lac Host Plant (Schleichera oleosa) - Kumar, Arvind; Singh, R. B. (Indian Forester, 2017)
A Lab experiment was conducted at Institute of Forest Productivity, Ranchi, and detailed biology and morphometrics of the litchi bug, Tessaratoma javanica Thunberg on Kusum (Schleichera oleosa) was studied. Adult and nymph both the stages were found to be infesting to the tender shoot of the plant. The tender shoot growing for lac insect, were the most preferred feeding site for this insect which causes a major shoot loss. Excessive feeding caused drying of growing buds and tender shoots and causes adverse plant growth. Adult female laid globular eggs on lower site of the leaf in a group. The life cycle was completed by the male and female 116.00 and 119.70 days, respectively.